An Efficient System for Gene Perturbation in Embryonic Hippocampal Progenitors Using Ex Vivo Electroporation Followed by In Vitro Dissociated Cell Culture. (18th April 2018) - Muralidharan, Bhavana; D'Souza, Leora; Tole, Shubha
We established an efficient cell culture assay that permits combinatorial genetic perturbations in hippocampal progenitors to examine cell-autonomous mechanisms of fate specification. The procedure begins with ex vivo electroporation of isolated, intact embryonic brains, in a manner similar to in utero electroporation but with greatly improved access and targeting. The electroporated region is then dissected and transiently maintained in organotypic explant culture, followed by dissociation and plating of cells on coverslips for in vitro culture. This assay recapitulates data obtained in vivo with respect to the neuron-glia cell fate switch and can be effectively used to test intrinsic or extrinsic factors that regulate this process. The advantages of this ex vivo procedure over in utero electroporation include the fact that distinct combinations of perturbative reagents can be introduced in different embryos from a single litter, and issues related to embryonic lethality of transgenic animals can be circumvented.